Formulation And Testing Of The Effectiveness Of The Ethanol Extract Lotion Of Rosella Flower (Hibiscus Sabdariffa L.) Lotion As A Skin Moisturizer - Felicia Kurnia; Tan Suyono; Ali Napiah Nasuyion; Sahna Ferdinan (International Journal of Health and Pharmaceutical (IJHP), 2022)
Rosella flowers are able to provide a moisturizing and smoothing effect because they contain many substances that are useful for the skin, rosella flowers are also synonymous with a sour taste so that it gives a fresh sensation. In this study, the ethanolic extract of rosella flowers used was at a concentration of 2%, 2.5%, 3%, and 5%. This type of research is experimental research using a pre-test and post-test control group design. The sample of this research is Rosella flower extract lotion (Hibiscus Sabdariffa L.). Data analysis using ANOVA. The results showed that the entire concentration group of rosella flower (Hibiscus Sabdariffa L.) ethanol extract in this study was effective in moisturizing the skin. Ethanol extract of rosella flower (Hibiscus Sabdariffa L.) which is most effective in moisturizing the skin is ethanol extract with a concentration of 5%. The entireconcentration group of Rosella flower (Hibiscus Sabdariffa L.) ethanol extract in this study was effective in smoothing the skin. The ethanol extract of rosella flower (Hibiscus Sabdariffa L.) which was most effective in smoothing the skin was ethanol extract with a concentration of 5%.